2015
DOI: 10.1158/1078-0432.ccr-14-2898
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Radiosensitivity Signature in Human Breast Cancer

Abstract: Purpose: An unmet clinical need in breast cancer management is the accurate identification of patients who will benefit from adjuvant radiotherapy. We hypothesized that integration of postradiation clonogenic survival data with gene expression data across breast cancer cell (BCC) lines would generate a radiation sensitivity signature (RSS) and identify patients with tumors refractive to conventional therapy.Experimental Design: Using clonogenic survival assays, we identified the surviving fraction (SF-2Gy) aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 29 publications
6
111
0
Order By: Relevance
“…Despite great progress in RT over recent years, locoregional recurrence and distant metastasis after RT remain key problems decreasing the survival of breast cancer patients [2]. Locoregional recurrence results from the presence or evolution of radioresistant tumor cells for which standard fractionated RT doses are sublethal[3]. Currently, there is a dearth of clinically available predictive biomarkers to indicate the optimal radiation dosing in breast cancer, which leads to suboptimal treatment of these patients[4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite great progress in RT over recent years, locoregional recurrence and distant metastasis after RT remain key problems decreasing the survival of breast cancer patients [2]. Locoregional recurrence results from the presence or evolution of radioresistant tumor cells for which standard fractionated RT doses are sublethal[3]. Currently, there is a dearth of clinically available predictive biomarkers to indicate the optimal radiation dosing in breast cancer, which leads to suboptimal treatment of these patients[4].…”
Section: Introductionmentioning
confidence: 99%
“…Ten-year receiver operating characteristic (ROC) curves (A) and Kaplan–Meier survival estimate (B) analysis in validation dataset of radiosensitivity in breast cancer using random forest machine learning (Speers et al , 2015). …”
Section: Figurementioning
confidence: 99%
“…However, locoregional recurrence rate differs by molecular subtypes, and triple negative and HER2-enriched subtypes have a higher risk of loco-regional recurrence despite radiotherapy (33). While there is an absolute need for greater precision in prescribing radiotherapy in patients with breast cancer, Speers and his colleagues formulated a molecular signature of radiation response from in vitro studies, and they found that there was no relationship between radiosensitivity and molecular subtype (34). Radiotherapy needs to be tailorable to tumour biology ranging from no treatment to partial breast irradiation and loco-regional irradiation, even including the internal mammary chain (35).…”
Section: Personalized Radiation Therapymentioning
confidence: 99%